Fixed-k inference for volatility - Tim Bollerslev; Jia Li; Zhipeng Liao (Quantitative Economics, 2021)
We present a new theory for the conduct of nonparametric inference about the latent spot volatility of a semimartingale asset price process. In contrast to existing theories based on the asymptotic notion of an increasing number of observations in local estimation blocks, our theory treats the estimation block size k as fixed. While the resulting spot volatility estimator is no longer consistent, the new theory permits the construction of asymptotically valid and easy-to-calculate pointwise confidence intervals for the volatility at any given point in time. Extending the theory to a high-dimensional inference setting with a growing number of estimation blocks further permits the construction of uniform confidence bands for the volatility path. An empirically realistically calibrated simulation study underscores the practical reliability of the new inference procedures. An empirical application based on intraday data for the S&P 500 equity index reveals highly significant abrupt changes, or jumps, in the market volatility at FOMC news announcement times, validating recent uses of various high-frequency-based identification schemes in asset pricing finance and monetary economics.
Keywords: C14; C22; C32; 330; Spot volatility; high-frequency identification; semimartingale; uniform inference